High-temperature granite magmatism, crust-mantle interaction and the mesoproterozoic intracontinental evolution of the Musgrave Province, Central Australia - Smithies, R.; Howard, H.; Evins, P.; Kirkland, Chris; Kelsey, D.; Hand, M.; Wingate, M.; Collins, A.; Belousova, E. (2011)
The Musgrave Province lies at the convergence of major structural trends formed during the Proterozoic amalgamation of the North, West and South Australian Cratons prior to c. 1290 Ma. The Musgrave Orogeny, one of three Mesoproterozoic orogenies to affect the province, produced the granites of the Pitjantjatjara Supersuite, which dominate the outcrop. This orogeny was an intracontinental and dominantly extensional event in which ultrahigh-temperature (UHT) conditions persisted from c. 1220 to c. 1120 Ma. The onset of UHT conditions is heralded by a change from low-Yb granites to voluminous Yb-enriched granites, reflecting a rapid decrease in crustal thickness. The Pitjantjatjara granites are ferroan, calc-alkalic to alkali-calcic rocks and include charnockites with an orthopyroxene-bearing primary mineralogy. They were emplaced at temperatures ≥1000°C from c. 1220 to c. 1150 Ma. Their geochemical and Nd and Hf isotopic homogeneity over a scale of >15 000 km2 reflects a similarly homogeneous source. This source included an old enriched felsic crustal component. However, the bulk source was mafic to intermediate in composition. The long-lived UHT regime, and thermal limits on the amount of crust sustainable below the level of intrusion, indicates a significant (>50%) mantle-derived source component.However, a positive correlation between Mg-number and F suggests that many Pitjantjatjara granites formed through the breakdown of F-rich biotite in a crustal granulite. We suggest that under- and intraplated mafic magmas assimilated the limited available felsic crust into lower crustal MASH (melting, assimilation, storage, homogenization) domains. These partially cooled but were remobilized during subsequent under- and intra-plating events to produce the Pitjantjatjara granites. The duration of UHT conditions is inconsistent with a mantle plume. It reflects an intracontinental lithospheric architecture where the Musgrave Province was rigidly fixed at the nexus of three thick cratonic masses. This ensured that any asthenospheric upwelling was focused beneath the province, providing a constant supply of both heat and mantle-derived magma.